SISTEM INFORMASI MAHASISWA BERPRESTASI UNIVERSITAS PALANGKA RAYA BERBASIS WEBSITE - Nova Noor Kamala Sari; Viktor Handrianus Pranatawijaya (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2021)
Outstanding students are the students who have achieved high achievements, both academically and non-academically. The information of these outstanding students of University of Palangka Raya is often not recorded properly. Thus, the institution collects and obtains the information manually from each faculty. So that the purpose of developing this website-based Outstanding Student Information System is to produce an information system that contains the profiles of the outstanding students from all study programs, departments and faculties of University of Palangka Raya. The software development method used is the waterfall method with saveral stages consisting of analysis, design, implementation, and testing. Collecting and processing the students’ achievement information with this website-based system is practically better than manual ones.